2018
DOI: 10.4085/1302148
|View full text |Cite
|
Sign up to set email alerts
|

Motivators, Anticipated Challenges, and Supportive Factors for Athletic Trainers Pursuing the Doctor of Athletic Training Degree

Abstract: Context: The doctor of athletic training degree (DAT) is a new concept in athletic training. Athletic trainers (ATs) currently pursue the degree, but little is known about why they choose the DAT. Objective: To explore ATs' motivations to pursue the DAT degree. Design: Qualitative study. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…2,3 Dedication to lifelong learning, critical thinking, and a desire to advance the profession are likely key factors associated with an athletic trainer's decision to pursue postprofessional education in an accredited residency program or DAT program. This is supported by Mulder et al, 7 who reported that DAT students chose to pursue their degree based on specific personal motivators of lifelong learning, advancement of the profession, and mentoring, among other reasons. Similar to our findings, advanced practice clinicians in physical therapy have been found 8 to pursue professional development and leadership activities at a greater rate than do peers who do not seek postprofessional training to achieve advanced clinical practice.…”
Section: Personal Attributesmentioning
confidence: 67%
“…2,3 Dedication to lifelong learning, critical thinking, and a desire to advance the profession are likely key factors associated with an athletic trainer's decision to pursue postprofessional education in an accredited residency program or DAT program. This is supported by Mulder et al, 7 who reported that DAT students chose to pursue their degree based on specific personal motivators of lifelong learning, advancement of the profession, and mentoring, among other reasons. Similar to our findings, advanced practice clinicians in physical therapy have been found 8 to pursue professional development and leadership activities at a greater rate than do peers who do not seek postprofessional training to achieve advanced clinical practice.…”
Section: Personal Attributesmentioning
confidence: 67%
“…Although not explicitly stated in the definition, as a clinical scholar with advanced knowledge and skills, these individuals would have the requisite knowledge to serve as both clinical and classroom educators and evidence has indicated a desire to utilize the degree within these employment opportunities. 3 The DAT programs vary in program curricular content, delivery mode, and area of focus, while also including advanced practice skill and/or leadership development. 4,5 There are several potential reasons to pursue this educational opportunity for athletic trainers and may include the shortage of clinically prepared leaders, the shortage of O n l i n e F i r s t terminally prepared athletic trainers to teach within post-baccalaureate degree programs, or the need to produce individuals to initiate and engage athletic trainers at higher levels of clinical reasoning.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Individuals pursuing a DAT degree have reported that they are committed to learning and believe that the degree will bring them professional advancement and development. 3 The nursing profession has been examining this type of advanced terminal degree for the past several years. Doctor of Nursing Practice (DNP) degrees were developed to prepare nurses with the competencies needed to improve health care systems through administrative leadership and advanced practice roles.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…2(p3) Although not explicitly stated in the definition, as clinical scholars with advanced knowledge and skills, these individuals would have the requisite knowledge to serve as both clinical and classroom educators, and a desire to use the degree in these employment opportunities has been shown. 3 The DAT programs vary in program curricular content, delivery mode, and area of focus while including advanced practice skills, leadership development, or both. 4,5 Several potential reasons for ATs to pursue this educational opportunity include the shortage of clinically prepared leaders, the shortage of terminally prepared ATs able to teach within postbaccalaureate degree programs, and the need to produce individuals who can initiate and engage ATs at higher levels of clinical reasoning.…”
mentioning
confidence: 99%